Psychological aspects of online learning implementation at Ukrainian universities - N. Tavrovetska; O. Veldbrekht (Mukachevo State University, 2023)
The relevance of the study lies in the fact that, unlike most European countries that returned to full-time education after the end of the coronavirus pandemic, Ukraine, due to active military operations on its territory, continued an online educational process for a long time and again faces the choice of a rational way of learning. That is why there is a need to evaluate all the weaknesses and strengths of the remote educational format. The purpose of the study is to analyse the advantages and disadvantages of implementing online education in Ukrainian universities during martial law. To achieve this purpose, a survey of 56 teachers of psychological disciplines with professional experience from 4 to 28 years was conducted; the answers received were analysed. The results showed that the advantages of online learning for students and teachers are common: mobility, high quality of digital content, partial automation of knowledge control, a variety of psychological and pedagogical tools, and stimulation of the development of digital and technological competence. The main problems of online learning for students are communication disorders: a lack of personality-oriented communication between peers, and a deepening of the social distance between students and teachers. In the field of psychological education, this disadvantage is closely related to the difficulty of mastering practical professional skills, which consist in organising trusting, close interaction between people. For teachers, this form of work offers wide opportunities for professional self-fulfilment, but at the same time is accompanied by overload, rapid emotional burnout, deterioration of health and quality of life. The paper substantiates the need to restore full-time education, considering the positive experience of online learning. The results of the study can become the basis for the development of practical measures aimed at preventing professional maladaptation of university teachers; combating the difficulties of socialisation and professionalisation of young people who received higher education during quarantine and martial law.